A Brief Review on Plant Disease Detection Using Image Processing Techniques - Jyoti; Kumar, Prince (International Journal of Computer Sciences and Engineering, 2019)
The crop cultivation plays a very important role within the agriculture. Presently, the loss of food is principally because of infected crops, that reflexively reduce the assembly rate, productivity per unit space and reduction in quality of economic part of the crops, as a result of the 70-80 per cent blackout in yield of crops is because of diseases caused by varied micro-organisms like bacterium, virus and fungi. The detection of unwellness on the plant could be a vital to stop loss of yield and also the quality of agricultural turn out. The symptoms will be ascertained on the components of the plants like leaf, stem, lesions, fruits and roots that area unit developed because of bound organic phenomenon and abiotic factors. The leaf shows the symptoms by modification in color, spots and gall like formation thereon. This identification or detection of the unwellness is completed by manual observation and infectious agent detection which may consume longer and should prove pricey. In agriculture analysis of automatic plant disease detection is crucial analysis topic because it could prove advantages in observant massive fields of crops, and therefore mechanically observe symptoms of unwellness as shortly as they seem on plant leaves. The digital image process could be a technique used for improvement of the image.